Improved Radial GRAPPA Calibration for Real-Time Free-Breathing Cardiac Imaging - Seiberlich, Nicole (2010)
In order to generate real-time, non-gated, free-breathing cardiac images, the undersampled radial trajectory combined with parallel imaging in the form of radial GRAPPA has shown promise. However, this method starts to fail at high undersampling factors due to the assumptions that must be made for the purposes of calibrating the GRAPPA weight sets. In this manuscript, a novel through-time radial GRAPPA calibration scheme is proposed which greatly improves image quality for the high acceleration factors required for real-time cardiac imaging. This through-time calibration method offers better image quality than standard radial GRAPPA, but it requires many additional calibration frames to be acquired. By combining the through-time calibration method proposed here with the standard through-k-space radial GRAPPA calibration method, images with high acceleration factors can be reconstructed using few calibration frames. Both the through-time and the hybrid through-time/through-k-space methods are investigated to determine the most advantageous calibration parameters for an R=6 in vivo short-axis cardiac image. Once the calibration parameters have been established, they are then used to reconstruct several in vivo real-time, free-breathing cardiac datasets with temporal resolutions better than 45ms, including one with a temporal resolution of 35ms and an in-plane resolution of 1.56mm(2).